Circadian blood pressure profile in various ischemic stroke subtypes - V. V. Mashin; L. A. Belova; D. V. Grishchuk; M. A. Albert (Кардиоваскулярная терапия и профилактика)
Aim. To study the effects of various risk factors (RF) and circadian blood pressure profile (BPP) on pathogenesis of various ischemic stroke (S) subtypes. Material and methods. In total, 60 ischemic stroke patients aged 38-68 years were examined. All participants underwent 24-hour BP monitoring (BPM). Results. Arterial hypertension (AH) was diagnosed in all participants. AH crises were more frequent in patients with lacunar S subtype. By night BP decrease, 36.6% of the patients were identified as dippers, 50% - non-dippers, 6.6% - night-peakers, and 6.67% - over-dippers. Too low and too great BP decline (non-dippers, over-dippers) were RF for atherotrombotic, cardioembolic, and lacunar S. Maximal speed of morning BP surge was typical for patients with lacunar S, non-dippers, and over-dippers. Conclusion. Ischemic S usually happened in the morning; lacunar S developed significantly more often at 4-10 am. In males, the most important risk factor was age, in females Р compromised family history, and left ventricular hypertrophy. Circadian BPP disturbances were RF for various S subtypes.